Melhoria de processos-chaves a partir da medição de Indicadores de Desempenho através da capacitação em Educação Corporativa à Distância . Um estudo de caso. - Mathias, Jose Ricardo Loretti (2009)
This research, based on case studies, whose main objective is to identify criteria and indicators through the process of corporate education at a distance for estimating the improvement of key business processes of a given area of a business. This study was motivated by difficulties of the companies measure the effectiveness of process improvement implemented by training employees via distance education using performance indicators that are measured by the areas of human resources, and especially the areas that require the training . Another motivating factor is the experience lived by the researcher, in investigations for some companies that adopt this mode of education. In this context, the researcher for a theoretical model grounded in the four levels of evaluation proposed by Kirkpatrick (1998) and the development of indicators on quality vision (Takashina, FLORES, 1995, Camargo, 2000; CAMPOS, 2001) and the vision of the management model used by the methodology of the Balanced Scorecard (Kaplan, Norton, 1997). The result of this research is to obtain an understanding of the relationships between criteria and indicators of training, improvements in key business processes and the possibility of designing a model that can be applied in other organizations regardless of industry in which they are embedded.